Türkiye’de savunma harcamalarının kaynak tahsisi açısından değerlendirilmesi (1985-1999 Dönemi) - Efendioğlu, Mustafa (My University, 1999)
Defense expenditures is a means for the continuity of existance of society and social political stability, in other words, it is the basic need to set the social economic relations. In addition to this basic need, today budget size decreases, in contrast to this needs increase every where so finding sources for defens expenditures is more important than yesterday. Between 1985-1999 years, MSB budget has the first place in defense budget with % 35,4. General budget's %12 is for defense. Other sources are, %18 Defense Industry Support Fund, %16 Foreign Helps,%9,8 NATO Enfranstrüktür Fund, % 10,7 Turkish Defense Funds, % 5,8 State-Firm Credits and %3,7 Special and helps for Turkish Armed Forces. Even all these sources, national percentage in defense sources is very low. If we look main system needs, percentage is % 21, If we look all sources national percentage is %65. Even all these sources, Turkish Armed Forces can not get own needs.These incomes getting spending from different state offices, can not be used well. To overcome this problem, in National Defense Ministry, a new organization must be and different units have to be in one hand.
Keywords: Ekonomi; Finansman ekonomisi; Savunma harcamaları